Leaf traits of clonal grasses responding to the ratios of ammonium to nitrate in a semi-arid grassland: leaf order matters. (26th December 2022) - Liu, Ruoxuan; Chen, Jungang; Ren, Zhengru; Chen, Xu; Lu, Haining; Zhang, Yuqiu; Zhang, Yunhai
Abstract: Leaf is the main organ of photosynthesis. Leaf phenotypic plasticity largely determines the adaptation of plants to enriched nitrogen (N) environments. However, it remains unclear whether the optimal number (proportion) of leaves representing the leaf traits of the whole plant is similar between ambient and N-enriched conditions. Moreover, whether alteration in ammonium (NH4 + -N) to nitrate (NO3 − -N) ratios in atmospheric N deposition will alter the optimal leaf number is unexplored. By adding three NH4 + -N/NO3 − -N ratios in a temperate grassland of northern China since 2014, three traits (leaf area, thickness and chlorophyll content) of two dominant clonal grasses, Leymus chinensis and Agropyron cristatum, were measured in August 2020. Results showed that under ambient conditions, the mean leaf area, thickness and chlorophyll content values of two fully expanded leaves were similar to these of all leaves at the plant level, except for the leaf area of L. chinensis, which needed five leaves (78.82% of leaves in the plant). The ratios of NH4 + -N/NO3 − -N increased the number of required sampled leaves and significantly changed the mean value of leaf traits and the maximum value along leaf order. Moreover, the ratios of NH4 + -N/NO3 − -N altered the trade-off among the three leaf traits, which is dependent on leaf order, by increasing leaf area and decreasing leaf thickness. Therefore, our study suggests that to better indicate the leaf traits' value of the whole plant under N-enriched conditions, measuring all fully expanded leaves or providing a suitable scaling-up parameter is needed. Graphical Abstract: